Forget Forgotten Stents: Review of Ureteral Stent Tracking Systems. Issue 6 (26th November 2021) - Krishna, Suprita; Abello, Alejandro; Steinberg, Peter
Abstract: Introduction: Our objective was to assess existing systems for tracking ureteral stents after urological surgery and determine if these systems impact the rate of retained and forgotten stents. Methods: We performed a scoping review using the search terms ("ureteral stents" "ureteral catheters" "nephroureteral stents" "nephroureteral catheters" or "double J stents") and ("tracking" or "lost stents" or "forgotten stents"). Two of the authors individually selected relevant articles based on title and abstract and performed full review of manuscripts and references. Results: Nine different studies focusing on forgotten ureteral stents were identified. Tracking mechanisms included electronic medical records algorithms, cellphone, chat or computer-based applications. Rates of lost or delayed removal of stents in hospitals prior to using a tracking system were 0%–13%. With a tracking mechanism, the rate of lost or delayed removal was reduced to 1% or less in the studies we identified. Conclusions: Stent tracking systems successfully reduced delayed removal of ureteral stents and reduced the rates of retained stents; however, these systems are institution specific, and no universal solution is readily available. Such a solution would be beneficial for the urological community to investigate further and for industry partners to invest in.